Lessons on effective communication from Taiwan Government to combat COVID-19 - Tallutondok, Eva Berthy; Hsieh, Chia-Jung (GHMJ (Global Health Management Journal), 2022)
This perspectives explain the extraordinary gap in cases and deaths between Indonesia and Taiwan. The paper will answer the question: Why does Taiwan have just 7 deaths while Indonesia reported 14,348 deaths in the first week of November 2020? What strategy did Taiwan's government employ to combat COVID-19? What lesson can be learned from Taiwan to combat Covid-19? The aim of this article is to identify lessons on effective communications strategy used by Taiwan's government that can affect government, health professionals, and population together to combat COVID-19.